A Machine-Checked, Type-Safe Model of Java Concurrency : Language, Virtual Machine, Memory Model, and Verified Compiler - Lochbihler, Andreas (KIT Scientific Publishing, 2012)
The Java programming language provides safety and security guarantees such as type safety and its security architecture. They distinguish it from other mainstream programming languages like C and C++. In this work, we develop a machine-checked model of concurrent Java and the Java memory model and investigate the impact of concurrency on these guarantees. From the formal model, we automatically obtain an executable verified compiler to bytecode and a validated virtual machine.